KONSERVASI WARISAN BUDAYA SEBAGAI PENYANGGA DESTINASI UNGGULAN KAWASAN BOROBUDUR: STUDI ATRAKSI WISATA DI SANGGAR KESENIAN KABUPATEN SLEMAN DAERAH ISTIMEWA YOGYAKARTA - Marimin; Riadi Darwis; Anang Sutono (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2017)
Borobudur in Magelang Regency is one of the areas included in the top 10 tourist destinations. For that must be support from the surrounding areas including Sleman Regency as buffer zone through art attractions and other cultural heritage. This study aims to obtain the existing art and cultural data and conservation conducted by related parties. The research method that the writer use is descriptive method with qualitative approach. The object is its attraction and conservation. Data collection techniques used include: observation, interview, and documentation study. Data gathering tools include: checklists, interview guides, and document tools. Technical analysis used is data reduction, data presentation, withdrawal and verification conclusion. The conclusions obtained show that (1) there are 1,350 art groups that live, grow, and develop until 2017 in Sleman District, Special Region of Yogyakarta; with its artistic variants include: dance, music art, literary arts, traditional theater, comedy, puppet art, puppet klitik art, puppet sembung art, art of dance drama. The arts groups that dominate them are kuda lumping, jatilan and reog (350 groups), (2) cultural development and preservation packaged in 12 cultural village programs; (3) Conservation efforts of cultural heritage include: (a) revitalization of art to be presented in the form of a rewritable text, (b) inventory of art potential, (c) establishment of aspects (association of arts workers) d) the presence of pamong or cultural overseers, and (e) the provision of arts tools for 12 sub-districts of 17 sub-districts.